Unsettling the Trump Baby: Learning from values and pedagogy in the early childhood nursery. Issue 3 (September 2022) - Robson, Jenny
The 2018 anti-Trump protest in London is dominated by an effigy, in the form of a balloon, that morphs President Donald Trump and childhood. Whilst this can be interpreted as a humorous act to ridicule Trump, a critical reading of the scene through a postmodern lens suggests that the image is an appropriation and manipulation of childhood. Trump masquerading as a baby becomes the 'vagabond' who is denied citizenship; she is a focus for negativity and fears, symbolising the values of hate and intolerance. The Trump Baby is vexing in the way it obscures knowledge of the agentic and competent child known within the nursery. The protesters exercise power as they mock and humiliate the Trump Baby in the protest and on social media. Such actions legitimatise hostile acts against children and prompt questions about the interdependency between children and adults in the both the construction of values and the realisation of children's citizenship. This paper considers a range of positions that adults could adopt in order to co-construct values with children and respect their status as citizens. In this way, nurseries can become forums where children's citizenship is both defended and nurtured.